Prevalence of abnormal glycemic and lipidemic status in an urban population of Bangladesh - Das, M; Hassan, Z; Faruque, O; Parial, R; Khalequzzaman, M; Ali, L (Journal of Bio-Science, 2012)
Context: Undiagnosed cases of diabetes mellitus constitute a major proportion of diabetic patients in the developing countries due to lack of proper screening and primary care facilities. Generation of evidence on undiagnosed cases is highly important for the estimation of the true burden of this disease. Objectives: The present study was undertaken to explore the proportion of undiagnosed diabetes and associated disorders in a middle aged Bangladeshi population living in the capital city of Bangladesh. Materials and Methods: Under a cross-sectional observational design a group of 254 middle aged (35-60 yrs) subjects (146? and 108) were included in the study who previously were unaware about the existence of diabetes or its complications. A 2-sample OGTT was done and blood glucose was estimated by glucose-oxidase method and Serum total cholesterol, HDL and TG by enzymatic colorimetric (Cholesterol Oxidase /Peroxidase, CHOD-PAP) method. Glycemic and other abnormalities were diagnosed and classified as per WHO criteria. Results: Out of the total 254 subjects 34 (15.1%) were found to have type 2 diabetes mellitus (T2DM) and 49 (19.29%) were prediabetics (24.5%-IFG, 75.5% -IGT and 20.4% had combined IFG-IGT). WHR (the indicator of central obesity) was present in higher proportions of diabetic (93.9%) and prediabetics (89.9%) compared to 76.0% control (?2=8.815; p=0.017). Male subjects had significantly higher central obesity compared to females both in the controls (t=3.929; p<0.0001) and in T2DM groups (t=2.608; p=0.015). Dyslipidemia (judged by triglyceride value) was present among 64.7% in T2DM, 40.8% in Prediabetes and 47.9% in the Controls). In Prediabetes group 80% males had dyslipidemia compared to 20% females (p=0.008). Conclusion: Almost twice the proportion of reported diabetic and prediabetic cases in Bangladesh is still undiagnosed and a substantial proportion of these cases have generalized as well as central obesity and dyslipidemia. J. bio-sci. 19: 1-6, 2011 DOI: http://dx.doi.org/10.3329/jbs.v19i0.12674